Examining Stress-Related Pathways of Substance Use Among Sexual Minority Women - McCabe, Connor Joseph (My University, 2019)
Alcohol and drug abuse among sexual minority women (SMW) is an increasingly recognized public health concern in the United States. Across a multitude of nationally-representative samples, SMW populations report higher rates of substance use and disorder across the lifespan. SMW also report greater levels of adversity in adolescence (Friedman et al., 2011; Hughes & Eliason, 2002). Although minority stress models suggest that higher levels of adversity may explain mental health disparity among sexual minority populations (Hatzenbuehler, 2009; Meyer, 2003), few studies have longitudinally examined the impact of adversity among SMW in predicting substance use and disorder in later life. Moreover, none have examined psychological mediators such as emotion dysregulation that have previously explained greater internalizing disorder among SMW (e.g., Hatzenbuehler et al., 2008), and none have examined moderators of this developmental pathway. The goal of this study was to examine the effect of adversity on co-developing emotion dysregulation and substance use among sexual minority and non-minority youth, and address moderators characterizing risk and protection for developing use. Data were drawn from 2,278 heterosexual and 173 sexual minority women who participated in the Pittsburgh Girls Study. The Pittsburgh Girls Study is a large, diverse sample of inner-city girls followed prospectively from age 5 to age 21, and contains a large longitudinal sample of SMW. Specifically, I tested whether greater adversity and rumination among sexual minority girls account for higher levels of substance use through young adulthood, and examined whether social support from peers and parents within adolescence buffers this proposed risk pathway. Missing data analysis, latent growth curve modeling, and multi-group structural equation modeling with structural invariance testing were used to test 1) whether sexual minority status predicted individual differences in level and change in rumination and substance use from adolescence through young adulthood; 2) whether rumination and adversity were direct and serial mediators explaining the relation between sexual minority status and developing substance use; and 3) whether relations between adversity, rumination, and substance use were moderated by sexual minority status and social support. Results suggested that SMW reported greater marijuana use at age 20, though were no different from heterosexual peers in the level and change in rumination or alcohol use through young adulthood. Across sexual orientation groups, social stress predicted greater rumination in late adolescence and less decline through young adulthood, as well as greater marijuana use by age 20. Finally, I found evidence of indirect effects of sexual minority status on rumination and young adult marijuana use through social stress: though not a serial mediation process, SMW reported greater social stress in adolescence, which in turn predicted greater adolescent rumination, less decline in rumination, and greater marijuana use in young adulthood.
Thesis (Ph.D.)--University of Washington, 2019
Keywords: Emotion regulation; Internalizing pathway; Minority stress; Sexual minority; Substance use; Clinical psychology; Developmental psychology; Psychology